2018
DOI: 10.1186/s12968-018-0444-0
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive characterization of myocardial and vascular phenotype in pediatric chronic kidney disease using cardiovascular magnetic resonance imaging

Abstract: BackgroundChildren with chronic kidney disease (CKD) have increased cardiovascular mortality. Identifying high-risk children who may benefit from further therapeutic intervention is difficult as cardiovascular abnormalities are subtle. Although transthoracic echocardiography may be used to detect sub-clinical abnormalities, it has well-known problems with reproducibility that limit its ability to accurately detect these changes. Cardiovascular magnetic resonance (CMR) is the reference standard method for asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Specifically, the renal patients had higher diastolic blood pressure and mean blood pressure, while the essential hypertension group had greater pulse pressure. These findings are in keeping with previous large studies of blood pressure in these populations [5, 19] and suggest differing vascular abnormalities. However, it is not possible to definitively characterize vascular phenotype using this information because of the important role of cardiac output in determining blood pressure.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Specifically, the renal patients had higher diastolic blood pressure and mean blood pressure, while the essential hypertension group had greater pulse pressure. These findings are in keeping with previous large studies of blood pressure in these populations [5, 19] and suggest differing vascular abnormalities. However, it is not possible to definitively characterize vascular phenotype using this information because of the important role of cardiac output in determining blood pressure.…”
Section: Discussionsupporting
confidence: 92%
“…The renal group was a subset of a previously examined group of pediatric chronic kidney disease patients who had been phenotyped using MRI [5]. Only renal patients with a confirmed diagnosis of hypertension were included in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with chronic kidney disease (CKD) have increased cardiovascular mortality. In this pediatric study of 120 children with mild, moderate and severe CKD, Cheang et al [182] found CMR evidence for LV remodeling and reduced systolic and diastolic myocardial velocities in the CKD population. They hypothesized that novel CMR biomarkers may be useful in the early detection of abnormalities in this population.…”
Section: Miscellaneous Topicsmentioning
confidence: 99%
“…10 The systolic left ventricular (LV ) function generally seems to be well preserved in children with ESRD as reported in previous studies with the use of 2-dimensional (2D) echocardiography and tissue Doppler measurements. [6][7][8][9]11,12 Speckle tracking echocardiography (STE) permits the evaluation of myocardial mechanics and eventually myocardial deformation. [13][14][15] Speckle tracking echocardiography allows the study of myocardial speed and movement at more than 1 point at the same time.…”
Section: Introductionmentioning
confidence: 99%